Efek Ekstrak Sambiloto (Andrographis paniculata Nees) pada Ekspresi Telomerase dari Kanker Payudara Tikus yang Diinduksi dengan DMBA - Yurika Sastyarina; Junaidi Khotib; Sukardiman Sukardiman (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2010)
ABSTRACT It has been well documented that chemical carcinogen, 7.12 dimethylbenz(a)anthracene (DMBA), plays a role in the incidence and growth of mammary cancer. Present study was designed to investigate the influence of Andrographis paniculata extract on telomerase activities on DMBA induced breast cancer in the female rat Sprague Dawley strain. DMBA-induced mammary cancer is a useful model to investigate the changes of epithelial cells that occur during mammary cancer progression. Mammary cancer model was induced 10 times twice a week by oral DMBA 20 mg/kg body weight. Mammary cancer occurred in 75 % animals nine weeks after oral administration of DMBA, it was represented with nodule on the mammary gland and the increasing of mammary gland volume compare with normal control F(1.8) = 731.711; p < 0.001. This study was also designed to investigate the effect of Andrographis paniculata extract mammary carcinoma induced by DMBA. Administration of three different dose of Andrographis paniculata (100 mg/kg, 300 mg/kg and 1000 mg/kg) had statistically different with mammary gland volume of DMBA treated rat F (4.17) = 92.777; p<0.05. So, Andrographis paniculata has significant effect on the treatment of DMBA-induced mammary carcinoma. The Epithelial cells were harvested on day 90 and stained with routine histology staining, hematoxylineosin, for morphological qualitative analysis, immunohistochemical examination. The lesions observed from the removed samples ranged widely from benign to malignant. The results showed that DMBA induce cell proliferation, nuclear irregularities, and numerous mitoses and induced cell necrosis. The effect of Andrographis paniculata inhibits cell proliferation and induces apoptosis in cancer cells. On immunohistochemical examination, it shows that Andrographis paniculata can stimulate of telomerase enzyme. Key word: Andrographis paniculata, DMBA, mammary cancer, cell proliferation ABSTRAK Telah dilakukan penelitian efek ekstrak sambiloto (Andrographis paniculata Nees) pada ekspresi telomerase terhadap kanker payudara tikus betina (Sprague dawley) yang diinduksi dengan 7,12 dimethylbenz(a)anthracene (DMBA) menggunakan metode imunohistokimia. Diketahui model kanker payudara dengan induksi DMBA untuk menginvestigasi perubahan dari sel epitel yang terjadi selama prorses karsinogenesis kanker payudara. Pemberian ekstrak sambiloto pada tikus yang mengalami kanker payudara menyebabkan penurunan volume tumor dan ditinjau dari aspek hispatologi dan imunohistokimia adanya ekstrak sambiloto menyebabkan penghambatan proliferasi sel, penurunan ekspresi telomerase dan meningkatkan apoptosis. Kata Kunci : Andrographis paniculata,DMBA, kanker payudara, proliferasi sel